Vitamin D Deficiency and the Presentation of Primary Hyperparathyroidism: A Mini Review - Niharika Yedla; Hyon Kim; Anupa Sharma; Xiangbing Wang (International Journal of Endocrinology)
The clinical presentation of primary hyperparathyroidism (PHPT) has evolved over the years from a symptomatic disorder to a predominantly asymptomatic condition. Altered vitamin D metabolism seems to play a role in the presentation of PHPT and may exacerbate the severity of disease. The epidemiology of PHPT differs in the developing versus the developed world, where more severe phenotypes occur in regions where vitamin D deficiency is common. Although it has been validated that patients with PHPT should be vitamin D sufficient, the threshold to supplement in relation to the severity of PHPT and the degree of vitamin D deficiency remains controversial. This review will highlight some of the controversy regarding vitamin D deficiency and the different phenotypes of PHPT.